A revision of the Neotropical spider genus Oligoxystre Vellard 1924 (Theraphosidae, Ischnocolinae) - Guadanucci, José Paulo Leite (Zootaxa, 2007)
The genus Oligoxystre Vellard 1924 is revised. Pseudoligoxystre Vol 2001 is synonymized with Oligoxystre and its typespecies, P. bolivianum Vol 2001, is considered valid. The type-specimen of Oligoxystre auratum Vellard 1924, type-species by original designation, is considered lost. No additional material matching the original description was found and therefore the species is diagnosed from the original description. Four new species, all from Brazil, are also described: O. caatinga, O. dominguense, O. tucuruiense, and O. rufoniger. Data on natural history of O. bolivianum from field and captivity observations are presented. The genus Cenobiopelma Mello-Leitão & Arlé 1934 ) is based upon Cenobiopelma mimeticum Mello-Leitão & Arlé 1934 for which no type was ever designated and hence both are considered nomina nuda.